Effect of contraction frequency on energy expenditure and substrate utilisation during upper and lower body exercise. Issue 1 (29th January 2004) - Kang, J; Hoffman, J R; Wendell, M; Walker, H; Hebert, M
Abstract : Objective: To examine the effect of contraction frequency on energy expenditure and substrate utilisation during upper (UE) and lower (LE) body exercise. Methods: Twenty four college students were recruited: 12 were tested on an arm ergometer, and the other 12 were tested on a leg ergometer. Each subject underwent three experimental trials on three separate days, and the three trials were presented in a randomised order. Each trial consisted of 10 minutes of arm cranking or leg cycling at 40, 60, or 80 rev/min, with power output being kept constant at 50 W. Steady state oxygen uptake (Vo 2 ) and respiratory exchange ratio (RER) were measured during each exercise. Energy expenditure was calculated from the steady state Vo 2 adjusted for substrate metabolism using RER. Carbohydrate and fat oxidation were calculated from Vo 2 and RER based on the assumption that protein breakdown contributes little to energy metabolism during exercise. Results: Energy expenditure was greater (p<0.05) at 80 rev/min than at 40 rev/min. No difference was found between 40 and 60 rev/min and between 60 and 80 rev/min during both UE and LE. During LE, carbohydrate oxidation was also higher at 80 rev/min than at 40 rev/min, whereas no difference in fat oxidation was found among all three pedal rates. During UE, no speed related differences in either carbohydrate or fat utilisation were observed. Conclusions: Pedalling at a greater frequency helped to maximise energy expenditure during exercise using UE or LE despite an unchanging power output. Whereas contraction frequency affects energy expenditure similarly during both UE and LE, its impact on carbohydrate utilisation appears to be influenced by exercise modality or relative exercise intensity.